Postdramatic Theatre of Director Christoph Marthaler - Shevchenko, Arina R.; Shevchenko, Elena N.; Salakhova, Aigul R. (Journal of History Culture and Art Research, 2017)
The present paper deals with the main tendencies of modern European theatre represented in the creativity of a famous Swiss director Christoph Marthaler. Drama and theatre of the end of the 20th – the beginning of the 21st century were exposed to radical transformation. This change has been reflected in the theory of postdramatic theatre. A contemporary theatre is becoming more visual. Nowadays natural theatrical synthesis of various arts – visual, plastic, verbal, musical becomes an intersection of all kinds of artistic and medial practices as it has never been before. The new drama and theatre decline mimesis as the main principle of attitude to reality, they do not depict and do not reflect life, but strive to create a magic and/or ritual space of performative living and a special type of communication with audience. These peculiarities of modern theatre get a vivid evocation in the works of Christoph Marthaler. Having entered into theatre from music, the director creates his own unique language of art. The article proves that Marthaler’s works are an individual model of postdramatic theatre. The author concludes that its main distinctive feature is to blur the border between musical and dramatic performance. Marthaler does not stage the play – the images appear from musical phrases, fleeting impressions, observations and dramatic improvisations. The analysis enables to claim that the theatre in a real process of performance replaces the mimetic acting today. The applied principles of drama analysis can be used in studying of the other contemporary postdramatic theatre’s models.